A Novel Approach for the Simulation of Xenopus laevis Tail Regeneration - Serlin, Zachary. (2017)
Abstract: A framework for predictively linking cell-level signaling with larger scale patterning in regeneration and growth has yet to be created within the field of regenerative biology. If this could be achieved, regeneration (controlled cell growth), cancer (uncontrolled cell growth), and birth defects (mispatterning of cell growth) could be more easily understood and manipulated. This thesis looks to create a framework to predict macroscopic regenerative morphology using level-set methods, a cellular-based control scheme, and a morphogen-based positioning field. The key contribution is defining velocity models for the control scheme that bridge microscopic and macroscopic scales. The novel control scheme proposed uses three control mechanisms to collectively mimic biological regeneration. Application to the simulation of Xenopus laevis tail regeneration suggests the utility of the proposed methods.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Jason Rife.; Committee: Behrouz Abedian, and Michael Levin.; Keywords: Mechanical engineering, Biology, and Developmental biology.